Bovine viral diarrhea (BVD): A review emphasizing on Iran perspective - Khezri, Mohammad (Journal of Advanced Veterinary and Animal Research, 2015)
Bovine viral diarrhea (BVD) is one of the most important diseases of cattle responsible for major economic losses in dairy industries of Iran. So far, no nationwide program has been taken in Iran to control and eradicate the disease. Moreover, until now, no vaccination program has been practiced against BVD in Iran, although the disease is prevailing in the country. For effective controlling of BVD, it is necessary to cull the affected animals, and new entry of BVD in the farm should be prevented. Focusing on biosecurity in systematic control programs of BVD can also reduce the risks of introduction and spread of other epizootic and zoonotic diseases, thereby improving both cattle health and welfare in general. In this review paper, an overview on BVD emphasizing on Iran perspective has been discussed focusing on clinical manifestations of BVD, routes of transmission of BVD virus (BVDV), its diagnostic methods and possible prevention strategies. http://dx.doi.org/10.5455/javar.2015.b92